Organic waste on survival and morphological parameters on stakes of Aloysia triphylla in the seasons. - Monteiro, Gean Charles [UNESP]; Schmidt, Denise; Caron, Braulio Otomar; Elli, Elvis Felipe (My University, 2018)
The present study aimed to evaluate the influence of organic waste produced on small farms, on survival and morphological parameters on stakes of Aloysia triphylla in different seasons. The experiment was carried out from 1 June 2012 to 30 May 2013, in the forest nursery in the Federal University of Santa Maria (UFSM), Campus Frederico Westphalen-RS. The experimental design was randomized blocks in a factorial scheme 4x6, with four seasons (fall, winter, spring and summer) and six combinations of substrates (100% commercial substrate Plantmax®; 25% organic compound + 75% commercial substrate Plantmax®, 50% organic compound + 50% commercial substrate Plantmax®; 75% organic compound + 25% commercial substrate Plantmax®; 100% organic compound; Plantmax® 50% + 50% coconut substrate), and each treatment was composed of 3 replicates, with 10 seedlings each assessment. Treatment of 50% coconut substrate + 50% Plantmax® and 100% Plantmax® provided the greatest survival in plant propagation by cuttings in Aloysia triphylla, when compared to the other substrates tested. The most recommended seasons for production of Aloysia triphylla seedlings are summer and fall, and spring presented the worst results for the studied variables. The commercial substrate can be replaced by 25% for organic waste without compromising the quality of seedlings and up to 50% in the warm seasons (summer and fall).
Resíduo orgânico na sobrevivência e parâmetros morfológicos em estacas de Aloysia triphylla nas estações do ano
Keywords: Medicinal plants; particle size; temperature